Dynamic changes in virus-induced volatiles in cotton modulate the orientation and oviposition behavior of the whitefly Bemisia tabaci - Nebapure, Suresh M.; Shankarganesh, Karuppan; Rajna, Salim; Naga, Kailash Chandra; Pandey, Dheerendra; Gambhir, Shubham; Praveen, Koovalamkadu Velayudhan; Subramanian, Sabtharishi (Frontiers in Physiology, 2022)
Manipulation of insect vector behavior by virus-induced plant volatiles is well known. But how the viral disease progression alters the plant volatiles and its effect on vector behavior remains less explored. Our studies tracked changes in volatile profile in progressive infection stages of cotton leaf curl virus (CLCuV) infected plants and their effect on B. tabaci behavior. Significant differences in virus titers were noticed between progressive infection stages showing distinct symptoms. Whiteflies initially settled on CLCuV infected plants, but their preference was shifted to healthy plants over time. GC-MS analysis revealed subtle quantitative/qualitative changes in volatile organic compounds (VOCs) between the healthy and selected CLCuV infection stages. VOCs such as hexanal, (E)-2-hexen-1-ol, (+)-α-pinene, (-)-β-pinene, (Z)-3-hexen-1-ol, (+)-sylvestrene, and (1S,2E,6E,10R)-3,7,11,11-tetramethylbicycloundeca-2,6-diene (Bicyclogermacrene) were associated with the infection stage showing upward curling of leaves; (E)-2-hexen-1-ol, β-myrcene, β-ocimene, and copaene were associated with the infection stage showing downward curling. Validation studies with eight synthetic VOCs indicated that 𝜸-terpinene elicited attraction to B. tabaci (Olfactometric Preference Index (OPI)=1.65), while β-ocimene exhibited strong repellence (OPI=0.64) and oviposition reduction (66.01 to 92.55%). Our studies have demonstrated that progression of CLCuV disease in cotton was associated with dynamic changes in volatile profile which influences the behavioural responses of whitefly, B.tabaci. Results have shown that VOCs such as (+)-α-pinene, (-)-β-pinene 𝜸-Terpinene, α-guaiene; 4- hydroxy- 4 methyl-2- pentanone and β-ocimene emitted from Begomovirus infected plants could be the driving force for early attraction and later repellence/oviposition deterrence of B. tabaci on virus-infected plants. The findings of this study offer scope for the management of whitefly, B. tabaci through semiochemicals.